A Novel Virtual Force Approach for Node Deployment in Wireless Sensor Network - Xiangyu Yu; Weipeng Huang; Junjian Lan; Xin Qian (2012 IEEE 8th International Conference on Distributed Computing in Sensor Systems, 2012)
The effectiveness of wireless sensor networks (WSN) depends on the coverage and connectivity provided by node deployment, which is one of the key topics in WSN. In this paper, a modified virtual force-based node self-deployment algorithm for nodes with mobility is proposed. In the virtual force-based approach, all nodes are seen as points subject to repulsive and attractive force exerted among them, nodes can move according to the calculated force. In the proposed approach, Delaunay triangulation is formed with these nodes, adjacent relationship is defined if two nodes are connected in the Delaunay diagram. Force can only be exerted from those adjacent nodes within the communication range. Simulation results showed that the proposed approach has higher coverage rate and faster convergence time than traditional virtual force algorithm.